1997
DOI: 10.1523/jneurosci.17-21-08536.1997
|View full text |Cite
|
Sign up to set email alerts
|

Rhinal Cortex Removal Produces Amnesia for Preoperatively Learned Discrimination Problems But Fails to Disrupt Postoperative Acquisition and Retention in Rhesus Monkeys

Abstract: To test whether the rhinal cortex (i.e., entorhinal and perirhinal cortex) plays a time-limited role in information storage, eight rhesus monkeys were trained to criterion on two sets of 60 object discrimination problems, one set at each of two different time periods separated by 15 weeks. After the monkeys had learned both sets, two groups balanced for preoperative acquisition rates were formed. One group received bilateral ablation of the rhinal cortex (n ϭ 4), and the other was retained as an unoperated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
82
3

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 50 publications
16
82
3
Order By: Relevance
“…As already noted, damage to the perirhinal͞entorhinal cortices produces a behavioral pattern that is just the opposite of the one observed here, namely an impairment in visual recognition memory but not in visual habit formation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(26)(27)(28). Further, each of these patterns differs from the one produced by damage to TE, which yields impairments in both types of visual learning and memory (31,32).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…As already noted, damage to the perirhinal͞entorhinal cortices produces a behavioral pattern that is just the opposite of the one observed here, namely an impairment in visual recognition memory but not in visual habit formation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(26)(27)(28). Further, each of these patterns differs from the one produced by damage to TE, which yields impairments in both types of visual learning and memory (31,32).…”
Section: Discussionmentioning
confidence: 42%
“…One of these targets, the inferior prefrontal convexity (1)(2)(3)(4)(5), is essential for short-term visual memory (6)(7)(8), whereas the second, the perirhinal͞ entorhinal cortices in the medial temporal lobe (9)(10)(11)(12)(13), is critical for the long-term recognition of visual stimuli and of their associations with other stimuli (14)(15)(16)(17)(18)(19)(20)(21)(22). Neither of these areas, however, seems to contribute substantially to still another type of visual learning known as visual habit formation (23)(24)(25)(26)(27)(28). Unlike the various forms of short-and long-term memory that allow cognitive retention of stimuli and of stimulus-stimulus associations, often after only a single presentation and on the basis of visual observation alone, habits are considered to be stimulus-response connections formed gradually through trial and error on the basis of differential reinforcement of the instrumental response (29,30).…”
mentioning
confidence: 99%
“…Thus, the monkeys had no difficulty discriminating the visual cues from one another. Third, previous studies have shown that monkeys with bilateral rhinal cortex removals can learn visual discrimination problems at the same rate as intact controls (36)(37)(38)(39). Therefore, it is likely that the deficit we observed is specific to learning the associations between visual cues and workload, as opposed to a visual perceptual impairment.…”
Section: Molecular Biological Approach In Monkeysmentioning
confidence: 66%
“…Recent work has shown that RA can follow lesions of the perirhinal cortex (Eacott, 1998;Myhrer & Wangen, 1996;Wiig, Cooper, & Bear, 1996), the entorhinal cortex (Cho et al, 1993;Cho & Kesner, 1996), and the PRER (Thornton, Rothblat, & Murray, 1997), in addition to lesions of the hippocampus (Bolhuis, Stewart, & Forrest, 1994;Kim, Clark, & Thompson, 1995;Kim & Fanselow, 1992;Salmon, Zola-Morgan, & Squire, 1987;Winocur, 1990;Zola-Morgan & Squire, 1990). However, few studies have directly compared the contribution of these different hippocampal components (but see Bolhuis et al, 1994;Wiig et al, 1996).…”
mentioning
confidence: 99%
“…This prediction follows from the straightforward reasoning that lesions of the hippocampus do not disrupt postoperative acquisition of discrimination learning (Vnek & Rothblat, 1996;Zola-Morgan et al, 1982). Given the recent studies implicating the perirhinal and/or the entorhinal cortex in retrograde and anterograde recognition memory (e.g., Cho et al, 1993;Cho & Kesner, 1996;Myhrer, 1992;Myhrer & Johannesen, 1995;Thornton et al, 1997), it is tenable that only damage including the rhinal cortex will interfere with memories formed prior to a lesion. Furthermore, inasmuch as the hippocampus is largely uninvolved in the processing of such nonrelational information, we may thus expect it to have no significant role in the consolidation of simple discriminations.…”
mentioning
confidence: 99%